(untitled) (Bangladesh Journal of Medical Education, 2014)
This cross-sectional descriptive type of study was conducted to explore the level of stress and depression and to find out the various socio-demographic, academic factors which act as barriers to study among undergraduate medical students of Bangladesh. The study was conducted at Dhaka Medical College during the period of April 2009 to June 2009. The students of 1st year to 5th year were the study population. A total of 425 students participated in the study. After taking proper approval from the concerned authority adopting convenient sampling technique data were collected through a self administered questionnaire with validated Kessler 10 psychological distress scale. The study revealed that only (1%) respondents were free from any sorts of psychological stress. Over one third (34.6%) had mild stress, (39.8%) moderate stress and about one fourth (24.9%) was suffering from severe stress according to Kessler 10 Psychological distress scale. A significant proportion of male respondents (73%) had moderate to severe psychological distress compared to the female respondents (56%) p<0.001. A significant higher proportion (56%) of those experiencing study pressure had moderate to severe stress as well (p<0.001). Having political affiliation, higher proportion of students (66%) reported no or mild stress. It is researchers opinion that politically affiliated students usually maintain good relationship with their teachers which help them to pass or they influence their teachers to bring result in their favor or teachers favor them to keep their position undisturbed. Lower proportion (34%) reported to have moderate to severe stress. The differences between politically affiliated and not politically affiliated groups are statistically significant p<0.001.This study demonstrates that factors which are responsible for students stress and depression are not similar in all countries. Sources of stress of our students should be checked out for the betterment of our students. The study recommended that need for intervention like social and psychological support to improve the quality of life of medical students. Students advisors should be provided who will train students about stress management. DOI: http://dx.doi.org/10.3329/bjme.v2i1.18130 Bangladesh Journal of Medical Education Vol.2(1) 2011: 6-9